Teachers' cultural perceptions of ICT in Nigerian schools - Uyouko, Arit Uyouko; Wong, Su Luan (Universiti Putra Malaysia Press, 2015)
This report explores concepts that had emerged, grown, or diminished in teachers’ cultural perceptions of the use of Information and Communications Technology (ICT) in Nigerian schools. Five Nigerian school teachers who were enrolled in a doctoral programme at a Malaysian university participated in this study that used a qualitative method with a case study strategy. Interviews were employed to collect data about teachers’ cultural perceptions of the use of ICT in Nigerian schools. Findings from the interviews revealed that although teachers held positive views about ICT use, they were discouraged by inadequate ICT facilities and limited access to computers in schools. There were also some reservations about the negative impact of ICT on students and the society as a whole. Nevertheless, the participants were optimistic that the Nigerian education system would benefit greatly in the long run if ICT was integrated effectively in education. Teachers are a key component in the delivery of technological innovation in the classroom, and findings from this study would give an insight into perceptions of teachers towards the use of ICT in the classroom. Such information would be helpful to policy makers and curriculum planners in their review of ICT policies to help improve the quality of education and transform Nigeria into a knowledge-based economy.